Forecasting Thinner Number 7 Sales Using ARIMA (Autoregressive Integrated Moving Average) Method - Luhur Arif Santoso; Boy Isma Putra; Ribangun Bamban Jakaria; Indah Apriliana Sari W (Procedia of Engineering and Life Science, 2022)
PT. DCN Indonesia is a paint distributor company. In the provision of paint and all devices including thinner often require a keepatan in its provider. This research is done to obtain thinner demand forecasting and determine the amount of stock that must be available in storage in order to at any time meet the impromptu demand that is one of the problems. ARIMA is a forecasting method that is suitable for such cases because it has advantages in the use of data with fluctuating patterns. The results achieved in this study got the ARIMA model (1, 0, 4) which means that the forecasting results are influenced by the results of observations one month ago san error four months ago. obtained the results of the sale of thinner of 8 liters and after going through the calculation of safety stock resulted in inventory planning calculations of 120 liters.